State-of-the-art methodologies used in preclinical studies to assess left ventricular diastolic and systolic function in mice, pitfalls and troubleshooting - Pironti, Gianluigi (Frontiers in Cardiovascular Medicine, 2023)
Cardiovascular diseases (CVD) are still the leading cause of death worldwide. The improved survival of patients with comorbidities such as type 2 diabetes, hypertension, obesity together with the extension of life expectancy contributes to raise the prevalence of CVD in the increasingly aged society. Therefore, a translational research platform that enables precise evaluation of cardiovascular function in healthy and disease condition and assess the efficacy of novel pharmacological treatments, could implement basic science and contribute to reduce CVD burden. Heart failure is a deadly syndrome characterized by the inability of the heart to meet the oxygen demands of the body (unless there is a compensatory increased of filling pressure) and can manifest either with reduced ejection fraction (HFrEF) or preserved ejection fraction (HFpEF). The development and progression of HFrEF is mostly attributable to impaired contractile performance (systole), while in HFpEF the main problem resides in decreased ability of left ventricle to relax and allow the blood filling (diastole). Murine preclinical models have been broadly used in research to understand pathophysiologic mechanisms of heart failure and test the efficacy of novel therapies. Several methods have been employed to characterise cardiac systolic and diastolic function including Pressure Volume (PV) loop hemodynamic analysis, echocardiography and Magnetic Resonance Imaging (MRI). The choice of one methodology or another depends on many aspects including budget available, skills of the operator and design of the study. The aim of this review is to discuss the importance of several methodologies that are commonly used to characterise the cardiovascular phenotype of preclinical models of heart failure highlighting advantages and limitation of each procedure. Although it requires highly skilled operators for execution, PV loop analysis represents the "gold standard" methodology that enables the assessment of left ventricular performance also independently of vascular loading conditions and heart rate, which conferee a really high physiologic importance to this procedure.